PENERAPAN WILDLIFE HAZARD MANAGEMENT SEBAGAI UPAYA KESELAMATAN PENERBANGAN DI BANDAR UDARA INTERNASIONAL JENDERAL AHMAD YANI SEMARANG - Siti Oktaviani; Siswi Jayanti; Ida Wahyuni (Jurnal Kesehatan Masyarakat, 2019)
Aviation safety is the main point that must be considered in the operation of the aircraft. Birds and wild animals have a very serious impact on aircraft operations and even potentially endanger flight safety. Jenderal Ahmad Yani International Airport Semarang has 2 unconfirmed bird and wild animal incidents between 2014 until 2017. Wildlife hazard management in the aerodrome is very important to reduce the impact of hazards that might be caused by wild birds and animal hazards. The purpose of this study was to analyze the application of wildlife hazard management at Jenderal Ahmad Yani International Airport Semarang as an aviation safety system. This research is qualitative research with a descriptive approach with the study of company documents and field observations. The subjects of this study were 4 main informants, including 2 Environment and terminal landside officers and 2 Apron movement controllers and also 2 triangulation informants, including 1 SMS & OSH officer and 1 SMS & OSH section head. The instruments in this study used in-depth interview guidelines and observation sheets. Based on the results of the study, Jenderal Ahmad Yani International Airport Semarang, in general, has Jenderal Ahmad Yani International Airport, Semarang, in general, has implemented wildlife hazard management in accordance with Regulation of the Director-General of Civil Aviation Number: SKEP / 42 / III / 2010 about advisory circular cars 139-03, wildlife hazard management on or in the vicinity of an aerodrome as an aviation safety system.